Factors affecting the severity and prognosis of visual damage in inhalational methanol poisoning - Shen, Hongyi; Zhong, Liu Xueying; Fu, Yue; Shao, Wanwen; Yang, Yan; Wang, Zhenyu; Yang, Hui (Frontiers in Medicine, 2023)
Background/aims Inhalational methanol poisoning could cause severe damage to visual function. This study analyzed the prognosis of correlation between the visual function and the relevant risk factors. Methods In this retrospective study, 14 patients had confirmed inhalational methanol poisoning, resulting in visual impairment in both eyes. The following tests were performed: laboratory tests, best corrected visual acuity (BCVA), intraocular pressure, slit lamp, fundus photography, visual field (VF), pattern visual evoked potential (P-VEP), flash electroretinogram (F-ERG), optical coherence tomography (OCT), and orbital or cranial magnetic resonance imaging (MRI). Results With active treatment, visual function improved to varying degrees in all 14 cases (28 eyes) in this study. The BCVA of 21 eyes declined to no light perception at the onset. Sixteen eyes showed different degrees of improvement after treatment, with the final BCVA (LogMar) mainly ranging from 2 to 3, and vision acuity stabilized after the fifth month. The VF pattern in the acute phase was mostly blind. Other VF patterns included the central visual island, large paracentral scotomas, hemipleural VF defects, and the temporal visual island. Retinal nerve fiber layer (RNFL) thickening was observed commonly in the acute phase (146.8±33.2 µm), which subsided in the first month, showed dramatic thinning at the third month, and then stabilized after the fifth month after onset. MRI showed that the main sites involved were optic nerve impairment, the optic disc, and retrobulbar segments. The basal ganglia region was the site most involved in the central nervous system (CNS). Conclusion Inhalational methanol poisoning could lead to severe impairment of visual function, and the prognosis of visual acuity (VA) was highly relevant to the risk factors of duration of toxic exposure, delayed admission, and degree of acidosis. Keywords Inhalational methanol poisoning; Visual function prognosis; Optic nerve impairment; Risk factors